The impact of optimal tariffs and taxes on agglomeration - Matthias Ross (Hamburg Institute of International Economics (HWWA), 2002)
This paper extends an economic geography model by tariffs to analyze their impact on welfare and sustainability of agglomerations. Policies with and without cooperation are compared, with the goal of maximizing aggregated welfare in the former and regional welfare in the latter case. The main result is that under cooperation poorer regions are worse off in two respects. In the short-run they loose even more welfare and in the long-run sustainable agglomerations in richer regions get more likely. Thus, although cooperation could generate aggregated welfare gains the potential losers face even in the short-run no incentive to remove tariffs unless they are compensated appropriately, for instance by transfers. In this sense transfers from the rich to the poor are not only a policy to reach the goal of equity but also a necessary precondition to reach aggregated efficiency.
Keywords: F15; H21; F13; R12; F42; 330; optimal tariffs; optimal taxation; policy coordination; economic geography; economic integration; Optimalzoll; Optimale Besteuerung; Strategische Handelspolitik; Internationale wirtschaftspolitische Koordination; Agglomerationseffekt; Neue ökonomische Geographie; Wohlfahrtseffekt; Theorie